Physicochemical Characterization and Seasonal Variations of PM10 Aerosols in a Harsh Environment - Hamdan, Nasser M.; Alawadhi, Hussain; Shameer, Mohamed (Frontiers in Environmental Science, 2021)
We have conducted a comprehensive sampling campaign of PM10 pollutants at a site next to a major highway, following standard protocols. Particulate matter (PM) total mass, and elemental and chemical compositions of the fine and coarse fractions of traffic-related pollutants were determined using several complementary techniques, including gravimetric analysis, x-ray fluorescence, scanning electron microscopy, energy dispersive spectroscopy, and x-ray diffraction. The PM mass concentrations show that PM10 is within acceptable international levels except during dust storms. Desert dust, crustal minerals, and sea salts are the major natural sources of PM10 pollution. Examples of these pollutants are quartz [SiO2], calcite [CaCO3], gypsum [CaSO4·2H2O], palygorskite [(Mg,Al)2Si4O10(OH)•4(H2O], chlorite-serpentine [(Mg,Fe)6AlSi3O10(OH)8], halite [NaCl] and nitratine [NaNO3]. Anthropogenic pollutants, such as mascagnite [(NH4)2SO4] and koktaite [(NH4)2Ca(SO4)2·H2O], were also observed to contribute to PM10. Trace elements such as Zn, Cu, Fe, Cr and Mn that are markers for traffic sources, Ni and V that are markers for heavy oil combustion, and Pb, which is attributed to industrial emissions, were also identified in PM10. Seasonal variation of the average total mass concentrations and the average mass concentration of natural elements show that the hot season is associated with higher pollution levels compared to the cold season due to increased dust events in the spring and summer. Correlation coefficients between elements have identified elements originating from common sources such as dust storms (e.g., Si, Ca, Al, Fe, Ti, Mn) and sea breeze (Cl and Na), in addition to anthropogenic elements. Enrichment factors calculations have identified elements that mainly have crustal origins, and elements that are partially or highly enriched by humans. Anthropogenic elements were more enriched during the cold season due to reduced human activities in the summer.